Memenangkan Pasar Pembiayaan: Studi Kasus Strategi Bisnis PT. Armada Finance di Makassar (ETNOSIA : Jurnal Etnografi Indonesia, 2017)
With the proliferation of finance companies, companies are always trying to be existed in the middle of business competition through various strategies to win the market without violating the relevant government regulation. This article aims to explore how to deal with financing breach agreement, the existing strategies applied by the company, and how these are related to the regulation of Bank Indonesia. The research findings indicate that as a profit organisation, PT. Armada Finance, apllies syariah principle on the basis of murabahah without violating the regulation of Bank Indonesia. Despite the fact that the transaction between the company and the customers is always pursued in accordance with the rules, in case of breach agreement which includes default, transfer of warranty, emblezzment of collateral, the completion is adjusted with the type of deviation and the risk resulted toward the company, without neglecting Islamic business ethics, as one of the uniqueness of this finance company. Various strategies have been applied by the company, not only those established institutionally, but also on the basis of individual creativity, and they are complementary in practice. As finance company is mushrooming and becomes more competitive, breakthrough related to strategies should always be improved and are in accordance with marke needs.
Keywords: Corporate culture; finance company; strategy; syariah; murabahah; institutional; creativity